Application of Digital Technologies in Law - Ludmila Grudtsina; Mehriban Elbrus kyzy Guliyeva; Sergei Zhdanov; Badma Sangadzhiev; Victor Shestak (Jurnal Cita Hukum, 2022)
The study’s purpose is to examine the nature, concepts, and grounds for the use of various types of digital technologies in law, to concisely and clearly outline the systematized foundations of scientific knowledge on the application of digital technologies in law and legislation on the example of the Russian Federation, with the involvement of legislative practices of foreign countries. Methods. The deductive method was the main method of the study, which allowed to consider the nature and foundations, forms, as well as methods of using digital technologies in law and legislation. In addition, the inductive method, the method of systemic scientific analysis, comparative legal and historical methods were used. The leading method underlying the solution of the issue is to study the legal foundations and features of the use of digital technologies in law. Results. The study proves the theoretical unsolved problem of scientific understanding of the types and forms of application of digital technologies in law on the example of the Russian Federation and some countries of the world. The authors argue that digital technologies store a large amount of information, thereby greatly simplifying the transaction system. It allows to quickly receive information and, as a result, significantly save time and speed up the process of transferring information